Authentication and authorisation in service-oriented grid architecture - Beshiri, Arbër; Mishev, Anastas (Inderscience Publishers (IEL), 2023)
Applications (services) nowadays request access to resources that are mostly distributed over the network (wide-area network). These applications usually rely on mediums like Grid Computing Infrastructure (GCI) that enable them to be executed. GCI has heterogeneous nature and supports security as an essential part in grid systems. Grid Security Infrastructure (GSI) is a technology standard for grid security. Authentication and even authorisation present a security challenge for grids. In this paper are discussed the authentication and authorisation infrastructures in the grid, including technologies that cover these two major parts in this domain. Here are surveyed the challenges that security encounters, respectively grid authentication mechanisms, grid authorisation mechanisms and models. The combination of the grid authorisation technologies and grid authentication technologies with authorisation infrastructures enables role-based and fine-grained authorisation. Such technologies provide promising solutions for service (resources) oriented grid architecture authentication and authorisation.
Keywords: grid, service-oriented grid architecture, authorisation, authentication, security